The World Of Themes Of Chustiy's Ghazals - Otakhanova Mahmuda Mamadaliyevna (Zien Journals, 2024)
This article analyses the thematic classification of ghazals in the lyrics of Chustiy (Nabikhan Khojayev), an amazing poet of the 20th century, and studies its specific features. It also discloses the high artistic skill of the poet in lyrics. The poet’s ghazals, included in the poetry collection “Hayatnoma”, “Sadoqat Gullari”, “Kongil Tilagi” and “Korguncha Khair Endi”, were analyzed for the first time, and the ideas were proved with specific examples. The analysis was carried out using comparative-historical, hermeneutic and biographical methods. When Chustiy wrote ghazals in lyric poetry, he continued the traditions of his great predecessors in this regard, and wrote mainly on romantic topics. He was able to create fresh verses mixing both tradition and the spirit of modernity. A number of such peculiarities are highlighted in the article
Keywords: ghazal; romantic ghazals; moral-educational ghazals